AC electrothermal assisted plasmonic biosensor for detection of low-concentration biological analytes. (August 2021) - Vafaie, Reza Hadjiaghaie; Heidarzadeh, Hamid
Highlights: Increasing transport of analyte to the receptor using ACET assisted SPR biosensor. Improvement the analyte-receptor binding reaction and hence the reaction speed. Sensitivity, and figure of merit are investigated in this structure. The sensitivity higher than 300 nm/RIU and FOM of higher than 40. It be applied to future sensors to detect low concentration biological analytes. Abstract: The main challenges of the surface plasmon resonances (SPR) based biosensors are mass transport limitations, which makes them more complicated in the detection of low-concentration biological analytes. In this research work, they were coupled to a microfluidic system in which the mass transport limitation in the reaction region improved by employing an AC electrothermal (ACET) concentrator. Multi-physical modeling based on finite-element-method was done to study an ACET-enhanced plasmonic biosensor inside a microfluid channel. The effect of vital parameters (like electrical excitation and analyte concentration) on ACET flow and equilibrium reaction time are investigated. The obtained numerical results reveal that the proposed method enhances the analyte-receptor binding reaction and effectively reduces the response time. To identify refractive index changes, the surface plasmon resonances of a 50 nm silver film on a glass substrate is used. The optical characteristics like sensitivity (S) and figure of merit (FOM) were obtained. The sensitivity of higher than 300 nm/RIU and FOM of higher than 40 are calculated. Our work can be applied to future sensors to detect low concentration biological analytes.